The Effect of Environmentally Friendly Transportation Implementation and Supporting Policies on Air Pollution Reduction in Central Kalimantan - Ade Risna Sari; Fatma Sarie; Sri Suparni; Muhammad Abi Berkah Nadi; Meutia Nadia Karunia (Westscience Press, 2024)
This research investigates the effect of green transport implementation and supporting policies on air pollution reduction in Central Kalimantan through quantitative analysis. The study employs survey methods to collect data from residents, policymakers, and stakeholders, focusing on perceptions of green transport adoption, policy effectiveness, and air quality. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) path modeling is utilized to analyze the relationships between latent constructs and test research hypotheses. The findings reveal significant positive associations between environmentally friendly transportation implementation, supporting policies, and air pollution reduction. Specifically, both green transport adoption and policy effectiveness are found to positively influence perceptions of air quality. The results underscore the importance of promoting sustainable transportation solutions and implementing effective policy interventions to mitigate air pollution and promote environmental sustainability in Central Kalimantan. These findings contribute valuable insights to the literature on green transport strategies, policy interventions, and air pollution reduction, informing evidence-based decision-making and guiding the development of targeted interventions to address environmental challenges in the region.